Pandangan Muhammad Iqbal tentang Dunia Materi - Syafiq Effendhy (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
This study focus on the concept of material world according to Muhammad Iqbal, which can strengther the faith of Allah.This research was conducted by studying literature through interpretation method and logical thinking.The result of the research shows that the material world is not a final and static product. The material world is the reality in the progressive movement which is always flowing and changing. It is an action, a flowing from chaos to cosmos, a life and consciousness as an impact of evolution process, which is unlimited. In this perspective, the material world factually is a self, like the self of man.